A potent aminonaphthalimide platinum(IV) complex with effective antitumor activities in vitro and in vivo displaying dual DNA damage effects on tumor cells. Issue 20 (15th October 2019) - Wang, Qingpeng; Chen, Yan; Li, Guoshuai; Zhao, Yanna; Liu, Zhifang; Zhang, Ruiyan; Liu, Min; Li, Dacheng; Han, Jun
Graphical abstract: Highlights: Potent aminonaphthalimide platinum(IV) complex were designed and reported. Displaying effective antitumor activities in vitro and in vivo . Exhibiting a dual DNA damage mechanism to tumor cells. Possessing much potential in overcoming drug resistance of cisplatin. Abstract: A new aminonaphthalimide platinum(IV) complex was developed by incorporating aminonaphthalimide, a DNA intercalator, into the platinum(IV) system. This complex displayed potent antitumor activities against all tested tumor cell lines in vitro and showed great potential in overcoming drug resistance of cisplatin. Moreover, it remarkably inhibited the growth of CT26 xenografts in BALB/c mice without severe side effects in vivo . Then, the compound exhibited a dual DNA damage antitumor mechanism that it could interact with DNA in tetravalent form via the naphthalimide group to cause DNA lesion, and the further liberation of platinum(II) complex after reduction would induce remarkable secondary damage to DNA. Meanwhile, it caused cell apoptosis through an intrinsic apoptosis pathway by up-regulating the expression of caspase 3 and caspase 9.